Diário de uma península: arqueologia das paisagens sensoriais de Maraú, Bahia - Araujo, Girleney Santos (2016)
Is it possible to understand how people who lived in the Peninsula of Marau were related to the environment through the senses? This is the central question that prompted this research. Based on the understanding that the landscapes are intimate meetings with the world we experience with all senses, this narrative aimed to present an interpretation of how the past residents elaborated their understanding of the world around them through the sensory experience arranged by the material culture they produced, taking into consideration that the landscape itself can be understood as a material and symbolic production. To achieve a consistent interpretation, it was necessary to deepen the criticism that the Phenomenology does about the science based on the sight and recognize that Archeology also supports the sight as a main way of analysis in its research. Sensory Archaeology attempts to correct this by bringing all the senses as ways to seek understanding of the human groups in the past. With the identification of six archaeological areas for prospecting, focus on two of them to set up my review and discuss the Sensory Landscapes in Marau, Bahia.